Deforestation and agricultural expansion in Brazil’s Amazon and Cerrado biomes: 2000-2024 - Mingoti, Rafael; da Silveira, Hilton Luis Ferraz (International Food Policy Research Institute, 2025)
The Amazon and Cerrado biomes, which together cover nearly two-thirds of Brazil, are critical to global ecological stability but face significant deforestation pressures driven by agriculture and livestock expansion. While the Cerrado, with its savanna-like vegetation, and the dense forests of the Amazon have distinct ecological characteristics, both have been similarly impacted by Brazil's rapid agricultural and infrastructural development. Historically, these biomes were sparsely occupied until the 20th century, when large-scale projects such as the Belém-Brasília and Trans-Amazonian highways facilitated settlement and land conversion. During the 1980s, agricultural frontiers expanded rapidly, especially in the Cerrado. Research by Embrapa introduced advanced soil management techniques and crop adaptation strategies, enabling efficient tropical agriculture and converting native vegetation into productive farmland for crops like soy and corn. In the Amazon, where soils are less fertile, large-scale cattle ranching dominated, leading to the establishment of the infamous "arc of deforestation" along major transport routes.